Effect of Target Fortification on Osmolality and Microbiological Safety of Human Milk Over Time. Issue 3 (March 2020) - Piemontese, Pasqua; Liotto, Nadia; Menis, Camilla; Mallardi, Domenica; Tabasso, Chiara; Perrone, Michela; Bezze, Elena; Plevani, Laura; Roggero, Paola; Mosca, Fabio
ABSTRACT: Objectives: The fortification of human milk can result in increased osmolality, which may be associated with adverse effects for preterm infants. To evaluate the effect of target fortification on the osmolality and microbiological safety of donor human milk and raw mature milk during the first 72 hours of storage. Methods: We performed target fortification of 63 pasteurized donor human milk (PDHM) and 54 raw mature milk (RMM) samples in a laminar flow hood. Osmolality (mOsm/kg) was evaluated before fortification (T0), immediately after fortification (T1), at 6 (T2), 24 (T3), 48 (T4), and 72 hours (T5) after fortification. Microbiological analysis was performed at T0, T4, and T5. During the study, all samples were stored at 4°C. Results: Mean osmolality at each study point for PDHM and RMM were, respectively: T0: 291.4 ± 11.0 versus 288.4 ± 5.6 ( P = 0.06); T1: 384.8 ± 16.7 versus 398.3 ± 23.7; T2: 393.9 ± 17.7 versus 410.1 ± 27.0; T3: 397.8 ± 17.6 versus 417.9 ± 26.1; T4: 400.0 ± 16.5 versus 420.2 ± 24.9; T5: 399.6 ± 16.5 versus 425.2 ± 25.8 ( P < 0.001 from T1 to T5). Microbiological analyses were negative at each study points for PDHM. At T0 16.1% of RMM samples had positive cultures, whereas the bacterial count remained stable thought the study. Conclusions: PDHM's osmolality increases during the first 6 hours after fortification and remains stable and safe until 72 hours. RMM's osmolality increases during the first 24 hours and remains stable and safe until 72 hours. The storage at 4°C and the manipulation of PDHM and RMM samples in a laminar flow hood seem to be safe and preserve the microbiological safety of fortified pasteurized human milk until 72 hours.